FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT LANSIA TERHADAP POSYANDU LANSIA DI KELURAHAN TERNATE TANJUNG LINGKUNGAN I KECAMATAN SINGKIL MANADO: FACTORS THAT INFLUENCE THE INTEREST OF THE ELDERLY IN THE ELDERLY POSYANDU IN KELURAHAN TERNATE TANJUNG ENVIRONMENT I, SINGKIL MANADO DISTRICT - Sri Wahyuni; Katrina Binei (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2021)
Posyandu elderly (Posyandu) is an integrated health services for the elderly public sector in certain regions that have been agreed. Posyandu is driven by the community as a group that aims to improve the coverage of health services so that the elderly form in accordance with the health care needs of the elderly. This study aims to determine the factors that affect the interests of the elderly to the elderly in the village posyandu eclectus promontory I kecamatan neighborhood Singkil Manado. This study was conducted using deskriptif analitik using cross sectional approach. The sampling technique is total sampling. The data collection was conducted using questionnaires subsequent data obtainden were processed using SPSS. 16 program to be analyzed with chi square test. The significance level (α =0,05). The conclusion of this research there is influence between knowledge (p-value = 0.000), distance (p-value = 0.000), and family support (p-value = 0.000). the Posyandu elderly <α 0.05.